Successful Ovarian Stimulation for Fertility Preservation in a Patient with Chronic Myeloid Leukemia: Switch from Nilotinib to Interferon‐α. (6th December 2017) - Gazdaru, Smaranda; Perey, Lucien; Rosselet, Anne; Mathevet, Patrice; Chalandon, Yves; Vulliemoz, Nicolas
Abstract : The development of tyrosine‐kinase inhibitors (TKIs) has improved survival of patients with chronic myeloid leukemia (CML). Some patients may become resistant to TKIs and require hematopoietic stem cell transplant (HSCT) that is highly gonadotoxic. Fertility preservation with ovarian stimulation might be indicated but is challenging if patients need to remain on TKIs until HSCT because TKIs may compromise follicular development and response to ovarian stimulation. We report the case of a patient with CML resistant to TKI and planned for an HSCT, in which treatment by TKI was replaced by interferon‐α before and during ovarian stimulation for fertility preservation. Successful ovarian stimulation was performed, allowing cryopreservation of nine zygotes. Hematopoietic stem cell transplantation was performed, and at present, 3 years later, the patient presents a sustained major molecular response. Abstract : A case of a patient with chronic myeloid leukemia resistant to tyrosine‐kinase inhibitors is reported.